2008
DOI: 10.3346/jkms.2008.23.5.884
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the Superficial Brachial Artery in Korean Cadavers

Abstract: The superficial brachial artery (SBA), a branch of the axillary artery, is one of the most common arterial variations in this area. While it is more vulnerable to accidental arterial injection or injury, it could be useful for the nourishment of a medial arm skin free flap. To analyze the relationship between the SBA of axillary origin and segmental variation of the axillary artery, we dissected 304 arms of Korean cadavers. We found an SBA of axillary origin in 12.2% of cadaveric arms. Unilateral occurrence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 7 publications
6
44
1
2
Order By: Relevance
“…Type Ib: the superficial brachial artery arose in between the origins of subscapular and circumflex humeral arteries. In type Ic: superficial brachial artery arose from the second part of the axillary artery [5]. The current case is somewhat similar to type Ic as reported by them, the only difference being the continuation of axillary artery as profunda brachii artery in our case.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Type Ib: the superficial brachial artery arose in between the origins of subscapular and circumflex humeral arteries. In type Ic: superficial brachial artery arose from the second part of the axillary artery [5]. The current case is somewhat similar to type Ic as reported by them, the only difference being the continuation of axillary artery as profunda brachii artery in our case.…”
Section: Discussionsupporting
confidence: 73%
“…The present variation may mislead the radiologists during colour Doppler studies and digital substraction studies. However, the present variation is useful in skin flaps like medial skin free flap Yang [5]. These variations should be given attention to because of their importance in microvascular and reconstruction surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,10,11 The findings of the present study regarding high origin of radial artery did not correlate with Rodriguez-Baeza et al (1995) who found the origin of radial artery from axillary artery in 10.66%. 12 (Table 1).…”
Section: Discussioncontrasting
confidence: 37%